The Gulf Cooperation Council A Rising Power and Lessons for ASEAN - Low, Linda (Institute of Southeast Asian Studies, 2011)
The Gulf Cooperation Council (GCC) is comprised of Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates. Possessing a significant share of the world's oil and gas reserves and including some of the world's fastest growing economies, the GCC is a significant regional grouping. As with the Association of Southeast Asian Nations (ASEAN), the Council has made significant progress towards economic integration. Seeking to draw out lessons applicable to ASEAN, this report looks at the structure and evolution of the GCC. This includes the context within which the Council was established, its rationale, and economic importance. It then follows the organization's development over time, paying particular importance to its progress from Customs Union and Common Market towards Monetary Union. The report then sets out the key challenges ahead for the Council, and concludes by highlighting the structural, organizational, and political lessons that resonate with ASEAN and its membership